2016
DOI: 10.1186/s12909-016-0672-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of simulation-based nursing education depending on fidelity: a meta-analysis

Abstract: BackgroundSimulation-based nursing education is an increasingly popular pedagogical approach. It provides students with opportunities to practice their clinical and decision-making skills through various real-life situational experiences. However, simulation approaches fall along a continuum ranging from low-fidelity to high-fidelity simulation. The purpose of this study was to determine the effect size of simulation-based educational interventions in nursing and compare effect sizes according to the fidelity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
283
2
34

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(326 citation statements)
references
References 18 publications
7
283
2
34
Order By: Relevance
“…5 A metaanalysis published in 2016 showed that the use of simulation improved learner satisfaction and selfconfidence. 13 It was used in the discipline: in HIV and tuberculosis.…”
Section:  Simulationmentioning
confidence: 99%
“…5 A metaanalysis published in 2016 showed that the use of simulation improved learner satisfaction and selfconfidence. 13 It was used in the discipline: in HIV and tuberculosis.…”
Section:  Simulationmentioning
confidence: 99%
“…Meta-analytic studies find simulationbased medical education to be effective with moderate to large effects [15][16][17]. In the educational setting, teachers may feel less prepared to implement interventions due to lack of opportunity to implement the model, noting supports such as video and practice would be the most effective in implementation skills [18].…”
Section: Journal Of Childhood and Developmental Disorders Issn 2472-1786mentioning
confidence: 99%
“…To achieve clinical competence, the traditional model of school nursing education combined with clinical placements is often considered the gold standard (Pai, 2016). However, nursing students' direct experience with or opportunities for patient care have been reduced (Kim et al, 2016) due to rapid changes in clinical placements, ethical concerns, and patient safety issues (Yip and Hsiao, 2014). As a useful pedagogical approach, simulation-based education provides nursing students with opportunities to handle various problem-based clinical situations by using patient simulators, such as handling manikins, engaging in roleplaying, and practicing on trained persons.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation involves a range of types and methods, from low-fidelity simulation to high-fidelity simulation (HFS) (Kim et al, 2016). There has been an increasing utilization of HFS in nursing education since the 1990s (Au et al, 2016).…”
Section: Introductionmentioning
confidence: 99%